2012
DOI: 10.1111/j.1708-8240.2012.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Incisal Translucency of Vital Natural Unrestored Teeth: A Clinical Study

Abstract: Statistically significant interaction (p < 0.001) was found for the groups. The interaction between race and gender was not statistically significant (p = 0.485). However, the interaction between race and age (p = 0.03), age and gender (p = 0.015), and among age, race, and gender (p < 0.001) was found statistically significant according to the analysis of variance test results. The interaction between race and gender was not statistically significant (p = 0.485).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 13 publications
1
27
0
3
Order By: Relevance
“…Bu konuda yapılan araştırmalar mevcuttur. 16,20,21 Yaşlı dentin veya sklerotik dentin daha koyudur (yoğunluk değeri yüksek, parlaklık değeri düşüktür). Genç dentin daha kırmızı-sarıyken yaşlı dentin daha çok yeşil-mavidir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu konuda yapılan araştırmalar mevcuttur. 16,20,21 Yaşlı dentin veya sklerotik dentin daha koyudur (yoğunluk değeri yüksek, parlaklık değeri düşüktür). Genç dentin daha kırmızı-sarıyken yaşlı dentin daha çok yeşil-mavidir.…”
Section: Discussionunclassified
“…ShadeScan herhangi bir aydınlatma koşulunda kullanı-labilir, çünkü halojen ışık, ortam ışığından etkilenmeyecek miktarda parlaktır. 16 Bilgisayar-destekli renk seçimi aynı kişi tarafından yapılmıştır. Her bir seçime başlarken, aletin ısınması üre-tici firmanın önerisi doğrultusunda beklenmiştir.…”
Section: Renk Seçimiunclassified
“…However, most other bleaching studies conducted in Caucasian populations have reported both HB and OB to be equally effective (9,(13)(14)(15)(16)(17)(18)(19). The disparity in findings may be attributed to differences in bleaching agent concentrations, total treatment time, and racial variance of human teeth (20)(21)(22)(23). Bleaching studies that compared different Asian ethnic groups (e.g., Chinese, Koreans, Japanese, and Malays) will be more relevant as dissimilarities arising from genetic alternations and environmental influences are anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical trials on dental bleaching have been conducted on Caucasian populations (9,(13)(14)(15)(16)(17)(18)(19). However, racial differences in tooth anatomy, dimensions, and translucency may influence the outcomes of dental bleaching (20)(21)(22)(23). Available literature on comparison of the degree of tooth color change associated with different bleaching techniques in Asian populations is scarce as are studies evaluating outcome satisfaction and preference of dental bleaching techniques among Asian patients (24).…”
Section: Introductionmentioning
confidence: 99%
“…Surface shade mapping with the standard software is in basic Vita Lumin shade designations. Higher-resolution shade mapping, additional shade guide designation conversions, and Hue/Value/Chroma values are optional with additional software for dental laboratories [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%